Strengthening graduate profile dimensions through local wisdom-based experiential learning in elementary science and social studies - Rila Pangestika; Mintasih Indriayu; Slamet Subiyantoro (Universitas Ahmad Dahlan, 2026)
Character formation among elementary school students faces increasing pressure from digital distractions, value erosion, and the demands of twenty-first-century competencies. Graduate Profile Dimensions (GPD) is the central character outcome across all subjects. Empirical evidence on culturally grounded interventions that strengthen these dimensions, however, remains limited. This study examined the effectiveness of an experiential learning model, grounded in the local wisdom of Giriwoyo, in strengthening four GPD dimensions during natural and social science instruction. The study employed a pre-experimental one-group pretest-posttest design with 17 fifth-grade students in a rural elementary school, selected through purposive sampling. A validated 31-item instrument measured four GPD dimensions before and after a three-session intervention that embedded the local wisdom of Giriwoyo in Kolb’s experiential learning cycle. The results showed a statistically significant improvement in students’ overall GPD achievement following the intervention, with the greatest gains observed in collaboration and creativity, while independence and critical reasoning improved more modestly. The novelty of the study lies in validating a subject-embedded GPD instrument and documenting a culturally anchored experiential model within the newly introduced 2025 deep learning policy, rather than the project-based contexts examined in prior work. The findings imply that local wisdom can function as a structured pedagogical resource for character education in natural and social science; however, the single-site design and small sample make the results context-specific and call for replication using control-group and longitudinal designs.